Prze-pisywanie romantyzmu? O jednej z poetyckich dykcji Aleksandra Wata - Pietrych, Krystyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-ansi-language: EN-US; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US">The article is an attempt to read Wiersze śródziemnomorskie (Mediterranean Poems) – one of the most prominent texts of the modernist Polish poet Aleksander Wat. The author is interested in the relation of this text with Romanticism, consisting not only in a variety of intertextual and aesthetic references, but, what is most significant, in the realization of a Romantic concept of subjectivity in the way of perceiving and experiencing the world. The author follows the demonstrations of this subjectivity in the consecutive fragments of the Mediterranean poem, indicating multifaceted character of Romantic trappings and dependencies, especially those of epistemological kind. This kind of reading of the Mediterranean poem inclines one to pose a fundamental question: why Wat, in a revisionist fashion, makes use of the Romantic diction in Mediterranean Poems, making of it a kind of a subcode of his own language? It happens so because the difficulties of modernist identity have their source in Romanticism, which, firstly, discovers the world as a domain of conflicting oppositions, secondly, – as a meditative consciousness questioning the substantive unity of the subject, thirdly, – subjectivity as a task to be realized by various types of articulations and narrations.